2016
DOI: 10.1371/journal.pone.0158354
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a New CellCollector to Isolate Circulating Tumor Cells from the Blood of Patients with Different Stages of Prostate Cancer and Clinical Outcomes - A Proof-of-Concept Study

Abstract: Background and MethodsCirculating tumor cells (CTCs) constitute a useful approach for personalized medicine. Nevertheless, the isolation of these cells remains very challenging because they rarely circulate in the blood. Another current problem is the cancer-specific characterization of these cells, which requires a method that allows for the molecular and immunocytochemical profiling of all captured cells. The purpose of our proof of concept study was to investigate the use of a medical wire (CellCollector, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 27 publications
0
57
1
Order By: Relevance
“…However, the number of isolated CTCs per sample was not significantly higher than obtained with the CellSearch system (CellSearch range 1–10, median 1.8; CellCollector range 1–12, median 2.4). Just recently, Theil and colleagues found a correlation between the number of CTCs captured by the CellCollector (cut off ≥5 CTCs) and overall survival18. However, this finding needs to be validated by additional and larger studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the number of isolated CTCs per sample was not significantly higher than obtained with the CellSearch system (CellSearch range 1–10, median 1.8; CellCollector range 1–12, median 2.4). Just recently, Theil and colleagues found a correlation between the number of CTCs captured by the CellCollector (cut off ≥5 CTCs) and overall survival18. However, this finding needs to be validated by additional and larger studies.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, EpCAM-based enrichment alone cannot detect all CTC subpopulations21. Moreover, the usual restriction of analyzing large blood volumes from cancer patients22 could be circumvented by the in vivo CellCollector capture system1718, which resulted in higher incidences of CTC detection as compared to the CellSearch system. However, the number of isolated CTCs per sample was not significantly higher than obtained with the CellSearch system (CellSearch range 1–10, median 1.8; CellCollector range 1–12, median 2.4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nearly 30% of PCa cases overexpress EGFR and that deregulation of EGFR-mediated signaling pathways is associated with poor clinical outcomes [16,17]. Theil et al detected tumor-associated transcripts of EGFR in patients with metastatic PCa in 42.8% using CellCollector [18]. Shaffer et al detected EGFR expression in 18/20 (90%) of CTCs in patients with metastatic PCa using the CellSearch system [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent literature from 2010-2015, over 35 different CTC methods were identified [4]. More new devices have been recently described [5][6][7][8][9]. CTC detection modalities have been well documented [10][11][12] and will not be covered in this review.…”
Section: Methods For Ctc Capture and Detectionmentioning
confidence: 99%